Smart education : case study of smart pre-school - Koh, Kai Lun (Nanyang Technological University, 2021)
In today’s ever-changing world, technology has become an integral part of life in many aspects. While there have been obvious innovations made in various sector, the education scene does not enjoy the same treatment compared to other sectors. Internationally, there has not been much articles about SMART Education as well as its potential implementation to bring about benefits to the younger generation. Specifically, there has not been very concrete frameworks as well as systematic approach for SMART Education. The education scene has immense potential in integrating technology to bring about benefits to various stakeholders, which will be discussed in this research paper. This research paper first introduces different enabling technologies and their capabilities. These enabling technologies include Artificial Intelligence (AI), Internet of Things (IoT), Big Data, Blockchain and many more. Upon understanding about how each technology work, we explore the need to introduce SMART Education and the concept behind it, followed by a SMART Education framework that is applicable at all levels of education. The SMART Education framework summarises the vision of SMART Education, which is to develop future-ready students holistically through state-of-the-art technology. SMART Education focuses on 2 key aspects, Smart Learning and Smart Campus, and has 3 key stakeholders, Students, Teachers and Technology. After discussing the SMART Education framework in detail, a SMART Education System Architecture is proposed as a form of design to bring out the intended outcomes of the SMART Education framework. There are 5 key layers to the proposed architecture: Perception layer, Network layer, Edge layer, Cloud layer and Application layer. To illustrate this better, a case study of preschool is explored, where we leverage on the SMART Education framework and System architecture, to develop a systematic technological roadmap for the preschool. Specific enabling technologies are also discussed to give more elaboration to the benefits and how it ties in with the SMART Education framework, as well as how the SMART Education System Architecture can be utilised.